The Legalization of the Right to Strike in Turkey in the 1960s - EMRE, YUNUS (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2-4 PARK SQUARE, MILTON PARK, ABINGDON OX14 4RN, OXON, ENGLAND, 2019)
In July 1963, two laws, the Trade Unions Act and the Collective Bargaining, Strike and Lockout Act, were enacted in the Turkish parliament. With these laws, free trade unionism became possible, and the working class emerged as a strong political power. The legalisation of the right to strike produced several unexpected results. The most important of these occurred in the political field. The right to strike and union legislation became crucial for the development of the left and the change in the Cumhuriyet Halk Partisi, CHP (Republican People's Party). The first half of the 1960s clearly demonstrated that the CHP's position had changed; first and foremost, in its political stand vis-a-vis labour and the labour movement. In this article, the main cornerstones in the legalization of the right to strike and the role of the CHP and Bulent Ecevit will be discussed.